2020
DOI: 10.2196/17018
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Self-Management for Patients With Lymphoma: Assessment of the Reach of Intervention of a Randomized Controlled Trial

Abstract: Background Randomized controlled trials (RCTs) often provide accurate estimates of the internal validity of an intervention but lack information on external validity (generalizability). We conducted an RCT on the effectiveness of a self-management intervention among patients with lymphoma in a population-based setting. Objective The objectives of the current study were to describe the proportion of RCT participants compared to all patients invited to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…A decrease was observed in anxiety and depression levels following web-based applications in the intervention group (p = .01). However, it was reported that the results would not represent the target population as the participation rate was 25% (Arts et al, 2020). In their study on the effects of e-health self-management application…”
Section: Characteristics Of the Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…A decrease was observed in anxiety and depression levels following web-based applications in the intervention group (p = .01). However, it was reported that the results would not represent the target population as the participation rate was 25% (Arts et al, 2020). In their study on the effects of e-health self-management application…”
Section: Characteristics Of the Studiesmentioning
confidence: 98%
“…In randomized controlled trials, analysis is required for therapeutic purposes, but in most studies, an "intention-to-treat (ITT) analysis" was not performed. The completed ITT and the number of patients lost during follow-up were clearly reported in five studies (Arts et al, 2020;Cheville et al, 2018;Ruland et al, 2010;Stevenson et al, 2020;van der Hout et al, 2020b). The results of the ITT analysis were not reported in only one study (van der Hout et al, 2020a).…”
Section: Risk Assessmentmentioning
confidence: 99%
See 3 more Smart Citations